Implementation of Anaerobic Soil Disinfestation in Florida Tomato Production - Bodh R. Paudel; Francesco Di Gioia; Qiang Zhu; Xin Zhao; Monica Ozores-Hampton; Marilyn E. Swisher; Kaylene Sattanno; Jason C. Hong; Erin N. Rosskopf (EDIS, 2019)
Anaerobic soil disinfestation (ASD) is a relatively new technique that appears to be a promising tool for soilborne pest management and crop production improvement. This new 5-page publication of the UF/IFAS Horticultural Sciences Department is intended to introduce ASD for Florida vegetable growers. Written by Bodh R. Paudel, Francesco Di Gioia, Qiang Zhu, Xin Zhao, Monica Ozores-Hampton, Marilyn E. Swisher, Kaylene Sattanno, Jason C. Hong, and Erin N. Rosskopf. https://edis.ifas.ufl.edu/hs1345